Risk perception and sexual behavior in HPV-vaccinated and unvaccinated young Colombian women (2014)
Objective To compare sexual behaviors and risk perception between young women vaccinated for HPV and unvaccinated Colombian women. Methods In a cross-sectional design study, 1436 women (231 adolescents, less than 18 years; 1205 young women, 18-26 years) completed a self-administered questionnaire between May 2011 and March 2012 in Bogotá, Colombia. Data from vaccinated and unvaccinated women were compared by descriptive statistics and multivariate models. Results Sexual risk behaviors were not associated with vaccination after adjustment for risk perception, age, educational level, and HPV knowledge. By contrast, vaccination was associated with higher routine Pap smear screening (odds ratio [OR], 2.35; 95% confidence interval [CI], 1.69-3.28), use of modern contraceptives (OR, 2.02; 95% CI, 1.26-3.22), and consistent use of condoms (OR, 1.49; 95% CI, 1.11-2.01). Vaccinated young women were more likely to have had sex (OR, 2.08; 95% CI, 1.56-2.78), but sexual debut among adolescents was not associated with vaccination. In bivariate and multivariate analyses, vaccination status was negatively associated with perceived risk of HPV infection, warts, and cervical cancer. There was no association between vaccination and perceived risk of sexually transmitted infections in any model. Conclusion No association was found between changes in risk perception after HPV vaccination and sexual risk behaviors. © 2014 International Federation of Gynecology and Obstetrics.